Analysis of the Economic Impact and Losses Due to Stunting of Toddlers in the Bangka Belitung Islands Province - Wulandari, Ayu; Fitriyanti, Eka (MediaTrend, 2023)
As the next generation of the nation and a state asset, the government needs serious attention to overcome the problem of stunting, this is because stunting not only causes health problems but can also cause economic losses. The perception that stunting is only related to health problems is not correct because based on an economic perspective, the importance of health factors for humans is related to the quality of human resources. One way or another, the quality of human resources (HR) is determined by health status, so the fact is that stunting which results in a decrease in labor productivity in the future will have an economic impact. This research aims to analyze the impact and economic losses due to stunting of toddlers in the Bangka Belitung Islands Province. This research is a quantitative descriptive research sourced from secondary data from 2018-2022 and primary data through in-depth interviews. The analysis was carried out using the Konig formula calculation and Correction Factor. The results stated that during the 2018-2022  there was a significant decrease in the prevalence of stunting in the Bangka Belitung Islands Province. Based on the estimation results for the 2018-2022 period, the average value of potential losses due to a 2 percent decrease in productivity is IDR. 219,545,886,933.18 or 0.28 percent of Gross Regional Domestic Product (GRDP). Meanwhile, the average potential loss with a 9 percent decrease in productivity over a period of 5 years is IDR. 987,956,491,199.33. or 1.27 percent of the Gross Regional Domestic Product (GRDP).